The Shelduck population of the Ythan estuary, Aberdeenshire - Patterson, I J; Young, C M; Tompa, F S (Wildfowl, 1974)
The Shelduck Tadorna tadorna is virtually a summer visitor on the Ythan Estuary, Aberdeenshire, with most of the local population absent from the moult migration in early July until all have returned in April. The mean population in May dropped from 210 in 1962-1964, to 160 in 1968-1969. Breeding success was low, with 24% of clutches lost and 76% of ducklings lost between hatching and fledging. 87% of fledgelings failed to return after their first year dispersal. This very low recruitment was inadequate to replace annual adult mortality of 20-34%, but there is some indication that breeding output was better in years with a lower May population.